1999
DOI: 10.1002/(sici)1096-8644(199912)110:4<457::aid-ajpa6>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

Daily energy expenditure across the course of lactation among urban Bangladeshi women

Abstract: Measures of energy intake of lactating women in developing countries show that intakes are often lower than those recommended by international bodies, while fat-mass losses are often substantially less than the 3-4 kg used in the calculations of recommendations, suggesting that physiological adaptation must be commonplace among such women. The cost of lactation may be met by reduction in energy expenditure, including reduced physical activity, as well as by mobilization of bodily soft tissue. However, daily en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…Loss of LBM exceeding that of fat mass have been reported for both Bengali and Swedish women (Rashid & Ulijaszek, 1999;Sadurskis et al, 1988), but in both cases the losses occurred early in the postpartum period (0 -2 months pp), rather than later (2.4 -9 months pp), as found in the Cali women. Absolute values for both energy intake and energy expenditure tended to be higher in the LACT women, suggesting higher energy turnover.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Loss of LBM exceeding that of fat mass have been reported for both Bengali and Swedish women (Rashid & Ulijaszek, 1999;Sadurskis et al, 1988), but in both cases the losses occurred early in the postpartum period (0 -2 months pp), rather than later (2.4 -9 months pp), as found in the Cali women. Absolute values for both energy intake and energy expenditure tended to be higher in the LACT women, suggesting higher energy turnover.…”
Section: Discussionmentioning
confidence: 83%
“…For example, lactating women in India, 1 -6 months pp (Madhavapeddi & Rao, 1992;Piers et al, 1995), and in Bangladesh, 2 -8 months pp (Rashid & Ulijaszek 1999), as well as food supplemented women in the Gambia, 3 -9 months pp (Lawrence et al, 1986) were essentially weight stable showing changes in body weight of less than 0.7 kg. In contrast, studies of lactating women in the Philippines, 1-8 months pp (Guillermo-Tuazon et al, 1992), as well as those in Europe (Forsum, et al, 1992;Sadurkis et al, 1988;van Raaij et al, 1991) reported weight losses of 1.3 -1.4 kg in lactating women 1 -7 months pp.…”
Section: Discussionmentioning
confidence: 99%
“…We excluded 14 of these from our review because of unclear methodologies or because reported results were general statements, percentages of weight loss that could be attributed to lactation, or were otherwise uninterpretable (1,(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24). Of the 28 remaining studies included in the review, 15 were prospective cohort studies (25-39), 1 retrospective cohort study (40), 1 cross-sectional study (41), and 11 case-series reports (4,(42)(43)(44)(45)(46)(47)(48)(49)(50)(51). According to the U.S. Preventive Services Task Force rating scale, Level I evidence is obtained from at least one proper randomized, controlled trial; Level II-1 evidence is obtained from well-designed controlled trials without randomization; Level II -2 evidence is obtained from welldesigned cohort or case-control analytic studies preferably from more than once center or research group; Level II-3 evidence is obtained from multiple-time series, with or without intervention, or dramatic results in uncontrolled experiments; and Level III evidence is opinions of respected authorities, based on clinical experience, descriptive studies, or reports of expert committees (11).…”
Section: Study Selectionmentioning
confidence: 99%
“…Participants included white, "healthy" affluent women from the United Kingdom or United States (4, 48) as well as rural or urban women from economically distressed areas of Bangladesh, Taiwan, and the Philippines (43,44,49). Likewise, definitions of breast-feeding were broad and included no specification other than self-reports for varying durations (range 12 weeks to 15 months postpartum) (43,44,48,50) or reports of "exclusive" or "full and satisfactory" breast-feeding (4,42,46,49). Manning-Dalton (45) described breast-feeding as a score percentage with ranges between 0% (no breast-feeding) and 100% (no supplementation to infant).…”
Section: Level III Studiesmentioning
confidence: 99%
“…Over 50% women in the country suffer from chronic energy deficiency [3]. Negative energy intake and chronic energy malnutrition are even higher among women low socio-economic group specially from rural areas [4,5]. Studies suggest that this situation has seen little improvement in past 20 years.…”
Section: Introductionmentioning
confidence: 99%